A zone-of-inhibition assay to screen for humoral antimicrobial activity in mosquito hemolymph - Morejon, Bianca; Michel, Kristin (Frontiers in Cellular and Infection Microbiology, 2023)
In insects, antibacterial immunity largely depends on the activation of downstream signaling and effector responses, leading to the synthesis and secretion of soluble effector molecules, such as antimicrobial peptides (AMPs). AMPs are acute infection response peptides secreted into the hemolymph upon bacterial stimulation. The transcription of innate immunity genes encoding for AMPs is highly dependent on several signaling cascade pathways, such as the Toll pathway. In the African malaria mosquito, Anopheles gambiae, AMPs hold a special interest as their upregulation have been shown to limit the growth of malaria parasites, bacteria, and fungi. Most of the current knowledge on the regulation of insect AMPs in microbial infection have been obtained from Drosophila. However, largely due to the lack of convenient assays, the regulation of antimicrobial activity in mosquito hemolymph is still not completely understood. In this study, we report a zone of inhibition assay to identify the contribution of AMPs and components of the Toll pathway to the antimicrobial activity of A. gambiae hemolymph. As a proof of principle, we demonstrate that Micrococcus luteus challenge induces antimicrobial activity in the adult female mosquito hemolymph, which is largely dependent on defensin 1. Moreover, by using RNAi to silence Cactus, REL1, and MyD88, we showed that Cactus kd induces antimicrobial activity in the mosquito hemolymph, whereas the antimicrobial activity in REL1 kd and MyD88 kd is reduced after challenge. Finally, while injection itself is not sufficient to induce antimicrobial activity, our results show that it primes the response to bacterial challenge. Our study provides information that increases our knowledge of the regulation of antimicrobial activity in response to microbial infections in mosquitoes. Furthermore, this assay represents an ex vivo medium throughput assay that can be used to determine the upstream regulatory elements of antimicrobial activity in A. gambiae hemolymph.